Development of an Integrated ISO Framework for College Libraries’ Functions and Activities - Mandal, Sukumar (Journal of Information and Knowledge, 2017)
ISO file creation is an important task in library automation and digitization activities. This paper discusses the creation of integrated ISO framework in Ubuntu operating system and, Remastersys, an open source software. The paper demonstrates development of six domain specific clusters in a single window based interface for functions like content creation, housekeeping operations, information retrieval system, digital media archiving, federated search system, community communication interaction. These six functions are merged into a single ISO file of size 4.7 G.B. The ISO file helps to achieve the objectives of installation and configuration of target college libraries. After creation of the file it’s required to write on DVD by using the brasero to create the Ubuntu Live DVD. This framework helps college librarians to manage their library operations and manage the users. The software tool can easily be accessed from this single window for easy management of college library functions and activities.